Using AIRS and ARM SGP Clear‐Sky Observations to Evaluate Meteorological Reanalyses: A Hyperspectral Radiance Closure Approach. Issue 20 (16th October 2018) - Chen, Xiuhong; Huang, Xianglei; Dong, Xiquan; Xi, Baike; Dolinar, Erica K.; Loeb, Norman G.; Kato, Seiji; Stackhouse, Paul W.; Bosilovich, Michael G.
Abstract: Using the ground‐based measurements from the Atmospheric Radiation Measurement (ARM) Southern Great Plains (SGP) site and spectral radiance from the Atmospheric Infrared Sounder (AIRS) on National Aeronautics and Space Administration Aqua, we evaluate the temperature and humidity profiles from European Center for Medium Range Weather Forecasting ERA‐Interim and Modern‐Era Retrospective analysis for Research and Applications Version 2 reanalyses. Four sets of synthetic AIRS spectra are calculated using 51 clear‐sky sounding profiles from the ARM SGP observations, the collocated AIRS L2 retrievals and the two reanalyses, respectively. A subset of AIRS channels sensitive to temperature, CO2, or H2 O but not to other trace gases is chosen and further categorized into different groups according to the peak altitudes of their weighting functions. Synthetic radiances are then compared to the observed AIRS radiances for each group. For all groups, the observed AIRS radiances agree well with the synthetic ones based on the ARM SGP soundings or the AIRS L2 retrievals. The brightness temperature (BT) differences are within ±0.5 K. For two reanalyses, BT differences in all temperature‐sensitive groups are generally within ±0.5 K; but the mean BT differences in all groups sensitive to both T and H2 O are negative. Together, they suggest a wet bias in the free troposphere in both reanalyses. Moreover, such BT differences can be seen in the analysis of AIRS clear‐sky radiances over the entire 30–40°N zone. A grid‐search retrieval suggests that 9–30% reduction for reanalysis humidity between 200 and 800 hPa is needed to correct such wet bias. Key Points: ERA Interim and MERRA‐2 reanalyses in terms of spectral radiances are evaluated Both reanalyses have a wet bias in the free troposphere, and such bias is persistent over the seasons and over the entire midlatitude zone The 9–30% reduction for 200‐ to 800‐hPa reanalysis humidity is needed in order to correct the wet bias identified in the comparison